2006
DOI: 10.1074/jbc.m602585200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α-Ketoglutaric Semialdehyde Dehydrogenase

Abstract: In the phylogenetic tree of the ALDH family, ␣KGSA dehydrogenase from A. brasilense falls into the succinic semialdehyde dehydrogenase (SSALDH) subfamily. Several putative ␣KGSA dehydrogenases from other bacteria belong to a different ALDH subfamily from SSALDH, suggesting strongly that their substrate specificities for ␣KGSA are acquired independently during the evolutionary stage. This is the first evidence of unique "convergent evolution" in the ALDH family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…solfataricus genome. The recently crystallized gluconolactonase from Xanthomonas campestris as well as the xylonolactonases/arabinolactonases from Azospirillum brasilense and Caulobacter crescentus belong to the same superfamily of SMP-30 proteins (284)(285)(286). In Hfx.…”
Section: Bacteria Eukaryamentioning
confidence: 99%
See 1 more Smart Citation
“…solfataricus genome. The recently crystallized gluconolactonase from Xanthomonas campestris as well as the xylonolactonases/arabinolactonases from Azospirillum brasilense and Caulobacter crescentus belong to the same superfamily of SMP-30 proteins (284)(285)(286). In Hfx.…”
Section: Bacteria Eukaryamentioning
confidence: 99%
“…brasilense and to the characterized KGSADH enzyme from Sul. solfataricus (SSO3117) (283)(284)(285). In Cau.…”
Section: ␣-Ketoglutarate Semialdehyde Dehydrogenasementioning
confidence: 99%
“…Previous work has shown that L-arabinose is degraded by a pathway that conceptually resembles the Entner-Doudoroff pathway (14). By analogy, L-arabinose is first oxidized to L-2-keto-3-deoxyarabonate (L-KDA) (15)(16)(17), which is then converted into ␣-ketoglurate in the case of fast-growing rhizobia (18)(19)(20) or to glycolaldehyde and pyruvate in the case of slow-growing species like B. japonicum (14). While pyruvate most likely is oxidized in the TCA cycle, the fate of glycolaldehyde has not been resolved yet.…”
mentioning
confidence: 99%
“…Although the genome sequence of A. brasilense NBRC 102289 is currently unavailable, the nucleotide sequences of several genes from this bacterium show very high similarities (ϳ98%) to those of Burkholderia lata (17,20,(29)(30)(31). Therefore, a homology search using the protein BLAST program was performed against the genome sequence of B. lata using the hypI and hypJ genes as the probe protein sequences.…”
Section: Resultsmentioning
confidence: 99%
“…We previously revealed that its type strain NBRC 102289 (ATCC 29145) possesses alternative pathways of L-arabinose (29)(30)(31) Plant (cell wall) Table 1. Homologous genes are indicated in the same color and correspond to those shown in panels A to C. Gray and TR genes are putative L-Hyp transporters and transcriptional regulators, respectively.…”
mentioning
confidence: 99%